Chitty Chitty Bang Bang and the race against time - Cottrell Boyce, Frank 1959-; Fleming, Ian (Macmillan Children's Books, 2012)
Chitty rescues the Tooting family from a hungry T. rex and takes the family on a tour of early New York among other places
Forts. von: Boyce, Cottrell: Chitty Chitty Bang Bang flies again
Keywords: Families -- Juvenile fiction; Automobiles -- Juvenile fiction; Adventure stories -- Juvenile fiction; Magic -- Juvenile fiction; Time travel -- Juvenile fiction; Family life; Automobiles; Magic; Time travel; Zeitreise; Familie; Tyrannosaurus rex; Adventure stories; Humorous stories; Children's stories; Kinderbuch